The influence of cutting conditions on surface roughness and chemical properties behaviour of CFRP during milling - Abd Halim, Nor Farah Huda; Dahnel, Aishah Najiah; Mustafa, A.M.; Shaharudin, N.S.; Tomadi, Siti Haryani; Ahmad, Zuraida; Adesta, E.Y.T.; Sulaiman, M.H. (Department Mechanical & Manufacturing Engineering Faculty of Engineering Universiti Putra Malaysia, 2024)
Secondary manufacturing process such as milling operation is needed for carbon fibre reinforced polymer (CFRP). Milling of CFRP is recommended to machine in a dry condition however, thermally degraded resin and reduction of the quality of the machined surface are always a major problem. Therefore, this paper discussed the effect of the cutting conditions such as dry, coolant and chilled air on the surface roughness and degradation of chemical properties of CFRP. Milling operation was carried out employing 170 m/min with different cutting conditions –dry, coolant and chilled air cutting conditions. Poor surface roughness was observed when milling of CFRP in dry cutting condition. Damages such as matrix smearing and thermally degraded resin was also observed on dry CFRP machined surface. It was also observed that the reduction of the maleimide (C=C) in dry machined surface suggested that further post-curing occurred when milling CFRP in a dry cutting conditions.